Mechanistic Insights into Simultaneous Removal of Copper, Cadmium and Arsenic from Water by Iron Oxide-Functionalized Magnetic Imogolite Nanocomposites - Escudey-Castro, A; Escudey-Castro, A; Pizarro-Arriagada, C; Pizarro-Arriagada, C; Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K; Maldonado-Hernandez, T; Maldonado-Hernandez, T (Elsevier B.V., 2020)
Imogolite and magnetic imogolite-Fe oxide nanocomposites (Imo-Fe50 and Imo-Fe25, at 50 and 25 % Fe loading (w/w), respectively) were synthesized and tested for the removal of aqueous copper (Cu), cadmium (Cd), and arsenic (As) pollutants. The materials were characterized by transmission electron microscopy, and specific surface area and isoelectric point measurements. The Fe-containing samples were additionally characterized by Mössbauer spectroscopy and vibrating-sample magnetometry. Significant differences were found in the morphological, electrophoretic, and magnetic characteristics between imogolite and the nanocomposites. The in-situ Fe-oxide precipitation process modified the active surface sites of the imogolite. The Fe–oxide, mainly magnetite, favored the contaminants’ adsorption over the pristine imogolite. The adsorption kinetics of these pollutants were adequately described by the pseudo-second order and intraparticle diffusion models. The kinetic models showed that surface adsorption was more important than intraparticle diffusion in the removal of the pollutants by all the adsorbents. The Langmuir-Freundlich model described the experimental adsorption data, and both nanocomposites showed greater adsorption capacity than the imogolite. The adsorption of Cu and Cd was sensitive to cationic competition, showing a decrease of the adsorption capacity when the two cations coexisted, while their adsorption increased in the presence of arsenate. © 2020 Elsevier B.V.